Carbon supported manganese-doped Cu 1.96 S catalyst, method for preparing the same, and use thereof
Patent Information
- Application Number
- CN202410431867.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-11
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2044-04-11
AI Technical Summary
[0003]但是,在实际应用中,一方面,金属硫化物的富还原特性,使其表面极易被氧化,进而造成催化活性的丧失
[0052]本申请与现有技术相比,其有益效果在于:
Smart Images

Figure CN118237046B_ABST
Abstract
Description
Technical Field
[0001] This application belongs to the field of water organic pollutant treatment technology, specifically relating to a carbon-supported manganese-doped Cu... 1.96 S catalysts, their preparation methods, and applications. Background Technology
[0002] Metal sulfides are widely used in electrochemical energy storage, photocatalysis, and advanced oxidation processes due to their abundant reserves on Earth, excellent electrical conductivity, and outstanding mechanical strength. The application of transition metal sulfides such as pyrite, chalcopyrite, and manganese sulfide in heterogeneous advanced oxidation processes is receiving increasing attention.
[0003] However, in practical applications, on the one hand, the reducing properties of metal sulfides make their surfaces highly susceptible to oxidation, leading to a loss of catalytic activity. For example, cuprous sulfide catalysts, which come into direct contact with wastewater in wastewater treatment, are more easily oxidized by oxidants and pollutants, resulting in a loss of catalytic activity. Furthermore, cuprous sulfide-based catalysts exhibit poor dispersion, are prone to agglomeration, and have limited electron transfer between different valence states of copper, resulting in a limited variety of free radicals generated during catalytic oxidation, which is insufficient to meet the actual wastewater treatment requirements.
[0004] On the other hand, existing heterogeneous advanced oxidation processes have low efficiency in treating saline chemical wastewater, mainly because the free radicals generated during catalytic oxidation are easily quenched by salt (various anions) in the water. The resulting secondary free radicals have short lifetimes and poor oxidizing power, making them difficult to effectively degrade pollutants. Furthermore, anions readily adsorb onto the positively charged reaction centers (metal sites) in the catalyst, increasing the steric hindrance for pollutant and oxide adsorption and thus reducing oxidation efficiency.
[0005] Therefore, the development of cuprous sulfide catalysts with stable catalytic activity and resistance to salt interference is of great significance for the engineering application of transition metal chalcogenides in saline chemical wastewater. Summary of the Invention
[0006] 1. The problem to be solved
[0007] This application addresses one of the problems in existing technologies, namely, the easy oxidation of the surface of cuprous sulfide-based catalysts and the low treatment efficiency of heterogeneous advanced oxidation in saline chemical wastewater, by providing a carbon-supported manganese-doped Cu... 1.96 S catalyst, its preparation method and application, carbon-supported manganese-doped Cu 1.96 The S catalyst is prepared using a Cu / Mn-BTC metal-organic framework co-grown with Cu / Mn as a precursor. It is produced by adsorption and mixing of the precursor with an organic sulfur source under anaerobic conditions, followed by anaerobic sintering. This catalyst is applied to the process of periodate degradation of water pollutants, especially in saline waters, with carbon-supported manganese-doped Cu.1.96 The S catalyst reacts directly with pollutants via a non-radical pathway that generates high-valence metals through a reaction with periodate, without being quenched by salt, thereby improving the degradation efficiency of pollutants under the interference of various anions.
[0008] 2. Technical Solution
[0009] To solve the above problems, the technical solution adopted in this application is as follows:
[0010] This application provides a carbon-supported manganese-doped Cu 1.96 S catalyst, the catalyst comprising:
[0011] Porous carbon layer;
[0012] The active component Cu distributed on the porous carbon layer 1.96 S;
[0013] Doped with the active ingredient Cu 1.96 The active ingredient MnS in S;
[0014] in:
[0015] Manganese (Mn) is doped into Cu via sulfides (MnS). 1.96 In S, used to enhance Cu 1.96 The catalytic activity of S;
[0016] The porous carbon layer can hinder the oxidation of active ingredients by wastewater and organic matter, and at the same time, it can provide electrons to active ingredients through chemical bonds.
[0017] This application also provides the above-mentioned carbon-supported manganese-doped Cu. 1.96 The method for preparing sulfur catalyst is based on metal-organic framework (MOF) derivatization. It uses a Cu / Mn co-grown Cu / Mn-BTC metal-organic framework as a precursor, which is prepared by adsorption and mixing of the precursor with an organic sulfur source under oxygen-free conditions followed by oxygen-free sintering. The specific steps include:
[0018] S1. Copper and manganese salts are added to an ethanol solution. The addition of ethanol prevents hydrolysis of the metal salts. After dissolution, trimesic acid (BTC) and N,N-dimethylformamide (DMF) are added. BTC acts as a ligand and coordinates with the metals (copper and manganese) in the DMF solution. When the solution becomes turbid, pure water is added and the mixture is stirred. Stirring is to inhibit the preferential growth of Cu-BTC at room temperature, thus preventing the co-growth of Cu / Mn-BTC. The stirred mixture is then hydrothermally heated, washed, and dried to obtain the metal-organic framework precursor Cu / Mn-BTC.
[0019] S2, the metal-organic framework precursor Cu / Mn-BTC obtained in S1 and 2,5-diaminobenzenesulfonic acid are added to a mixed solution of ethanol and methanol, and adsorbed in a hydrogen-argon (H2 / Ar) mixed gas. The ethanol and methanol in the adsorbed mixed liquid are removed to obtain a precursor mixed powder. The hydrogen-argon mixed gas is used as a protective gas to assist the adsorption of 2,5-diaminobenzenesulfonic acid, so that the sulfur source and the precursor can be in full contact to ensure the subsequent in-situ sulfidation step, while creating a reducing atmosphere to prevent the Cu / Mn-BTC metal-organic framework precursor from being oxidized by oxygen.
[0020] In step S3, the precursor mixed powder obtained in step S2 is transferred to a tube furnace and sintered in an oxygen-free environment under argon (Ar) protection. This oxygen-free sintering method induces in-situ sulfidation and carbonization of the precursor mixed powder. The sintering temperature is 500–700℃, the sintering time is 3–6 hours, and the heating rate is 2–4℃ / min, yielding carbon-loaded manganese-doped Cu. 1.96 S catalyst.
[0021] Furthermore, in S1 above, the molar ratio of Cu:Mn:BTC is 2:1:4.
[0022] Further, in S1 above, the copper salt includes any one or more of copper chloride, copper sulfate, and copper nitrate. Further, in S1 above, the copper salt includes copper chloride.
[0023] Further, in S1 above, the manganese salt includes any one or more of manganese chloride, manganese sulfate, and manganese nitrate. Further, in S1 above, the manganese salt includes manganese chloride.
[0024] Furthermore, in S1 above, the amount of DMF used is 2-3 ml relative to 0.001 mol of Mn. Even further, in S1 above, the amount of DMF used is 2.5 ml relative to 0.001 mol of Mn.
[0025] Further, in S1 above, the volume ratio of DMF, ethanol, and pure aqueous solution is 1:(1.5~2):(1.2~1.5). Even further, in S1 above, the volume ratio of DMF, ethanol, and pure aqueous solution is 1:1.6:1.3.
[0026] Furthermore, in S1 above, the stirring includes stirring at 25–40°C for 6–10 hours. Even further, in S1 above, the stirring includes stirring at 30°C for 8 hours.
[0027] Furthermore, in S1 above, hydrothermal refers to hydrothermal treatment in a hydrothermal reactor.
[0028] Furthermore, in S1 above, the hydrothermal process includes hydrothermal heating at 100–130°C for 16–32 hours. Even further, in S1 above, the hydrothermal process includes hydrothermal heating at 120°C for 24 hours.
[0029] Furthermore, in S1 above, washing includes washing multiple times with ethanol and DMF solution, such as 10 times.
[0030] Furthermore, in S1 above, drying includes drying using a vacuum oven at a temperature of approximately 40°C.
[0031] Further, in S2 above, the mass ratio of the metal-organic framework precursor Cu / Mn-BTC to 2,5-diaminobenzenesulfonic acid is 1:(2.5~3.5). Even further, in S2 above, the mass ratio of the metal-organic framework precursor Cu / Mn-BTC to 2,5-diaminobenzenesulfonic acid is 1:3.
[0032] Furthermore, in S2 above, the volume ratio of ethanol to methanol in the ethanol-methanol mixed solution is 1:(1.5-3). Even further, in S2 above, the volume ratio of ethanol to methanol in the ethanol-methanol mixed solution is 1:2.
[0033] Furthermore, in S2 above, the mass fraction of hydrogen in the hydrogen-argon mixture ranges from 2% to 10%. Even further, in S2 above, the mass fraction of hydrogen in the hydrogen-argon mixture ranges from 5%.
[0034] Furthermore, in the above S2, the adsorption time includes 6 to 12 hours. Even further, in the above S2, the adsorption time includes 10 hours.
[0035] Furthermore, in S2 above, removing ethanol and methanol from the adsorbed mixed liquid includes drying in a vacuum oven at a temperature of about 40°C, and evaporating to remove ethanol and methanol.
[0036] Furthermore, in the above S3, the sintering temperature is 550℃~700℃, 600℃~700℃, or 650℃~700℃.
[0037] Furthermore, in the above S3, the sintering temperature is 500℃, 550℃, 600℃, 650℃, or 700℃. Even further, in the above S3, the sintering temperature is 550℃.
[0038] Furthermore, in the above S3, the sintering time is 3.5-6 hours, 4-6 hours, 4.5-6 hours, 5-6 hours, and 5.5-6 hours.
[0039] Furthermore, in the above S3, the sintering time is 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, and 5.5 hours. Even further, in the above S3, the sintering time is 3.5 hours.
[0040] Furthermore, in S3 above, the heating rate is 2, 3, or 4 °C / min. Even further, in S3 above, the heating rate is 3 °C / min.
[0041] Furthermore, in S3 above, the sintering temperature is 550℃, the sintering time is 3.5 hours, and the heating rate is 3℃ / min, to obtain carbon-supported manganese-doped Cu. 1.96 S catalyst.
[0042] Furthermore, in S3 above, the carbon-supported manganese-doped Cu obtained 1.96 The S catalyst is cleaned with ethanol and pure water to remove surface impurities and then dried at around 70°C.
[0043] This application also provides the above-mentioned carbon-supported manganese-doped Cu. 1.96 Application of S catalyst in the degradation of water pollutants by periodate, carbon-supported manganese-doped Cu 1.96 The S catalyst activates periodate to produce high-valence metals, thereby degrading pollutants.
[0044] Furthermore, the pollutants in the aforementioned water bodies include nitrogen-containing heterocyclic organic compounds.
[0045] Furthermore, the aforementioned water bodies include saline water bodies, such as saline chemical wastewater and carbon-loaded manganese-doped Cu. 1.96 The S catalyst activates periodate to generate high-valence metals to degrade pollutants. The high-valence metals directly transfer electrons with the pollutants without involving free radical reactions. This non-free radical reaction can avoid the influence of salt (inorganic anions) on the oxidation process, thereby improving the degradation efficiency.
[0046] Furthermore, the aforementioned salts include inorganic salts such as NaCl, Na2SO4, NaNO3, Na2CO3, and NaH2PO4.
[0047] Furthermore, the concentration of the above-mentioned salt is 5–35 g / L (0.5%–3.5%).
[0048] Furthermore, the concentrations of the aforementioned salts are 10–35, 15–35, 20–35, 25–35, and 30–35 g / L.
[0049] Furthermore, the concentration of the above-mentioned salt is 10, 15, 20, 25 or 30 g / L.
[0050] Furthermore, the concentration of the above-mentioned salt is 20 or 30 g / L.
[0051] 3. Beneficial effects
[0052] Compared with the prior art, the advantages of this application are as follows:
[0053] (1) This application provides a carbon-supported manganese-doped Cu 1.96 S catalyst, its preparation method and application, carbon-supported manganese-doped Cu 1.96 The S catalyst uses a Cu / Mn-BTC metal-organic framework (MOF) co-grown with Cu / Mn as a precursor. It is prepared by adsorption and mixing the precursor with an organic sulfur source under anaerobic conditions, followed by anaerobic sintering. The MOF precursor ensures uniform dispersion of sulfides on the carbon material. Furthermore, the in-situ carbonization of the MOF not only mitigates the oxidation of metal sulfides by organic matter and oxidants during wastewater treatment but also provides electrons to the metal sulfides, thus ensuring the overall activity and long-term stable use of the catalyst. In addition, manganese doping can alter the Cu... 1.96 The electron configuration inside S regulates Cu 1.96 S is involved in the active oxidation process to generate active oxidants, thereby improving the catalyst's efficiency in degrading pollutants.
[0054] (2) This application provides a carbon-supported manganese-doped Cu 1.96 S catalysts, their preparation methods and applications, carbon-supported manganese-doped Cu 1.96 S catalyst is used in the process of periodate degradation of water pollutants, especially in saline water, with carbon-supported manganese-doped Cu. 1.96 The S catalyst directly oxidizes pollutants via a non-radical pathway, generating high-valence metals through reaction with periodate, unaffected by salt quenching. This improves the degradation efficiency of pollutants under various anion interferences. Simultaneously, the metal sulfide and carbon loading allow sulfur to draw electrons from both the metal and carbon, weakening the positive charge of the metal center. This reduces the steric hindrance effect of salt (anions) on the catalyst, ensuring sufficient contact between the catalyst, oxidant, and pollutants, thus reducing the impact of carbon-loaded manganese-doped Cu. 1.96 The interference of salt on the mass transfer efficiency of S catalysts during catalytic oxidation can effectively improve the targeted removal of characteristic pollutants by metal sulfide catalysts in practical engineering. Attached Figure Description
[0055] Figure 1 It is the carbon-supported manganese-doped Cu prepared in Example 1 1.96 X-ray diffraction (XRD) pattern of the S catalyst.
[0056] Figure 2 Carbon-supported manganese-doped Cu prepared in Comparative Example 1 1.96 X-ray diffraction (XRD) pattern of the S catalyst.
[0057] Figure 3 It is the carbon-supported manganese-doped Cu prepared in Example 1 1.96 Scanning electron microscope (SEM) image of the S catalyst.
[0058] Figure 4 These are the results of a quenching experiment simulating wastewater.
[0059] Figure 5 These are the results of a saline simulated wastewater experiment.
[0060] Figure 6 This is the result of wastewater treatment in the production of pharmaceutical intermediates. Detailed Implementation
[0061] The present application will be further described below with reference to specific embodiments.
[0062] It should be noted that terms such as "upper", "lower", "left", "right", and "middle" used in this specification are only for clarity of description and are not intended to limit the scope of implementation. Changes or adjustments to their relative relationships, without substantially altering the technical content, should also be considered as within the scope of this application.
[0063] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains; the term “and / or” as used herein includes any and all combinations of one or more of the associated listed items.
[0064] Unless otherwise specified in the examples, the procedures should be performed under standard conditions or conditions recommended by the manufacturer. Reagents or instruments whose manufacturers are not specified are all commercially available products.
[0065] As used herein, the term “about” is used to provide for the flexibility and imprecision associated with a given term, measure, or value. Those skilled in the art can readily determine the degree of flexibility for a particular variable.
[0066] As used herein, the term “at least one of…” is intended to be synonymous with “one or more of…”. For example, “at least one of A, B, and C” explicitly includes only A, only B, only C, and combinations thereof.
[0067] Concentration, amount, and other numerical data may be presented in range format herein. It should be understood that such range format is used solely for convenience and brevity and should be flexibly interpreted to include not only the values explicitly stated as the limits of the range, but also all individual values or subranges encompassed within the range, as if each value and subrange were explicitly stated. For example, a range of values from about 1 to about 4.5 should be interpreted to include not only the explicitly stated limits of 1 to 4.5, but also individual numbers (such as 2, 3, 4) and subranges (such as 1 to 3, 2 to 4, etc.). The same principle applies to ranges that describe only a single value, such as “less than about 4.5,” which should be interpreted to include all the aforementioned values and ranges. Furthermore, this interpretation should apply regardless of the breadth of the range or characteristic described.
[0068] Example 1
[0069] This embodiment provides a carbon-supported manganese-doped Cu 1.96 S catalyst and its preparation method.
[0070] A carbon-supported manganese-doped Cu 1.96 S catalyst, the catalyst comprising:
[0071] Porous carbon layer;
[0072] The active component Cu distributed on the porous carbon layer 1.96 S;
[0073] Doped with the active ingredient Cu 1.96 The active ingredient MnS in S.
[0074] Its preparation method is based on metal-organic framework (MOF) derivation. It uses Cu / Mn-BTC co-grown MOF as a precursor, and prepares the MOF by adsorption and mixing of the precursor with an organic sulfur source under oxygen-free conditions followed by oxygen-free sintering. The specific steps include:
[0075] S1, weigh 0.8 g manganese chloride tetrahydrate (0.004 mol) and 1.4 g copper chloride dihydrate (0.008 mol) and add them to 16 ml of ethanol solution; after dissolving, add 3.39 g trimesic acid (BTC) (0.016 mol) and 10 ml of N,N-dimethylformamide (DMF) solution. BTC acts as a ligand and coordinates with the metals (copper and manganese) in the DMF solution; when the solution becomes turbid, add 13 ml of pure water and stir at 30 °C for 8 hours, then transfer to an autoclave and hydrothermally heat at 120 °C for 24 hours to obtain the metal-organic framework precursor Cu / Mn-BTC; wash 10 times with ethanol and DMF solution and immediately transfer to a vacuum oven to dry at 40 °C for later use;
[0076] S2, Weigh 0.2g of the metal-organic framework precursor Cu / Mn-BTC and 0.6g of 2,5-diaminobenzenesulfonic acid, add an ethanol / methanol solution with a volume ratio of 1:2, and adsorb for 10 hours under the protection of a hydrogen-argon mixed gas with a mass ratio of 5:95. Then dry in a vacuum oven at 40℃, evaporate and remove ethanol and methanol to obtain a precursor mixed powder.
[0077] S3. The precursor mixture powder obtained in S2 was transferred to a tube furnace and sintered in an oxygen-free environment under argon (Ar) protection at a sintering temperature of 550℃ for 3.5 hours at a heating rate of 3℃ / min. Surface impurities were removed by washing with ethanol and pure water, and the powder was dried at approximately 70℃ to obtain carbon-supported manganese-doped Cu. 1.96 S catalyst.
[0078] Example 2
[0079] This embodiment provides a carbon-supported manganese-doped Cu 1.96 S catalyst and its preparation method.
[0080] A carbon-supported manganese-doped Cu 1.96 S catalyst, the catalyst comprising:
[0081] Porous carbon layer;
[0082] The active component Cu distributed on the porous carbon layer 1.96 S;
[0083] Doped with the active ingredient Cu 1.96 The active ingredient MnS in S.
[0084] Its preparation method is based on metal-organic framework (MOF) derivation. It uses Cu / Mn-BTC co-grown MOF as a precursor, and prepares the MOF by adsorption and mixing of the precursor with an organic sulfur source under oxygen-free conditions followed by oxygen-free sintering. The specific steps include:
[0085] S1, weigh 0.8 g manganese chloride tetrahydrate (0.004 mol) and 1.4 g copper chloride dihydrate (0.008 mol) and add them to 12 ml of ethanol solution; after dissolving, add 3.39 g trimesic acid (BTC) (0.016 mol) and 8 ml of N,N-dimethylformamide (DMF) solution. BTC acts as a ligand and coordinates with the metals (copper and manganese) in the DMF solution; when the solution becomes turbid, add 9.6 ml of pure water and stir at 25 °C for 10 hours, then transfer to an autoclave and hydrothermally heat at 100 °C for 32 hours to obtain the metal-organic framework precursor Cu / Mn-BTC; wash 10 times with ethanol and DMF solution and immediately transfer to a vacuum oven to dry at 40 °C for later use;
[0086] S2, Weigh 0.2g of the metal-organic framework precursor Cu / Mn-BTC and 0.5g of 2,5-diaminobenzenesulfonic acid, add an ethanol / methanol solution with a volume ratio of 1:1.5, and adsorb for 6 hours under the protection of a hydrogen-argon mixed gas with a mass ratio of 2:98. Then dry in a vacuum oven at 40℃, evaporate and remove ethanol and methanol to obtain a precursor mixed powder.
[0087] S3. The precursor mixture powder obtained in S2 was transferred to a tube furnace and sintered in an oxygen-free environment under argon (Ar) protection at a temperature of 500℃ for 6 hours at a heating rate of 2℃ / min. Surface impurities were removed by washing with ethanol and pure water, and the powder was dried at approximately 70℃ to obtain carbon-supported manganese-doped Cu. 1.96 S catalyst.
[0088] Example 3
[0089] This embodiment provides a carbon-supported manganese-doped Cu 1.96 S catalyst and its preparation method.
[0090] A carbon-supported manganese-doped Cu 1.96 S catalyst, the catalyst comprising:
[0091] Porous carbon layer;
[0092] The active component Cu distributed on the porous carbon layer 1.96 S;
[0093] Doped with the active ingredient Cu 1.96 The active ingredient MnS in S.
[0094] Its preparation method is based on metal-organic framework (MOF) derivation. It uses Cu / Mn-BTC co-grown MOF as a precursor, and prepares the MOF by adsorption and mixing of the precursor with an organic sulfur source under oxygen-free conditions followed by oxygen-free sintering. The specific steps include:
[0095] S1, weigh 0.8 g manganese chloride tetrahydrate (0.004 mol) and 1.4 g copper chloride dihydrate (0.008 mol) and add them to 24 ml of ethanol solution; after dissolving, add 3.39 g trimesic acid (BTC) (0.016 mol) and 12 ml of N,N-dimethylformamide (DMF) solution. BTC acts as a ligand and coordinates with the metals (copper and manganese) in the DMF solution; when the solution becomes turbid, add 18 ml of pure water and stir at 40 °C for 6 hours, then transfer to an autoclave and hydrothermally heat at 130 °C for 16 hours to obtain the metal-organic framework precursor Cu / Mn-BTC; wash 10 times with ethanol and DMF solution and immediately transfer to a vacuum oven to dry at 40 °C for later use;
[0096] S2, Weigh 0.2g of the metal-organic framework precursor Cu / Mn-BTC and 0.7g of 2,5-diaminobenzenesulfonic acid, add an ethanol / methanol solution with a volume ratio of 1:3, and adsorb for 12 hours under the protection of a hydrogen-argon mixed gas with a mass ratio of 10:90. Then dry in a vacuum oven at 40℃, evaporate and remove ethanol and methanol to obtain a precursor mixed powder.
[0097] S3. The precursor mixture powder obtained in S2 was transferred to a tube furnace and sintered in an oxygen-free environment under argon (Ar) protection at a temperature of 700℃ for 3 hours at a heating rate of 4℃ / min. Surface impurities were removed by washing with ethanol and pure water, and the powder was dried at approximately 70℃ to obtain carbon-supported manganese-doped Cu. 1.96 S catalyst.
[0098] Comparative Example 1
[0099] This comparative example provides a carbon-supported manganese-doped Cu. 1.96 S catalyst and its preparation method.
[0100] The same metal-organic framework precursor preparation steps as in Example 1 are used, except that the sintering temperature in step S3 is 800°C.
[0101] Example 4
[0102] This embodiment provides carbon-supported manganese-doped Cu prepared in Example 1 and Comparative Example 1. 1.96 Characterization of the S catalyst. This includes:
[0103] (1) X-ray diffraction
[0104] Carbon-supported manganese-doped Cu prepared in Example 1 1.96 The X-ray diffraction (XRD) results of the S catalyst are as follows: Figure 1 As shown, carbon-supported manganese-doped Cu 1.96 S catalyst with Cu 1.96 The material, in which S is the main phase, also contains a MnS phase, indicating that manganese is doped into Cu via MnS. 1.96 S in.
[0105] Comparative Example 1: Carbon-supported manganese-doped Cu 1.96 The X-ray diffraction (XRD) results of the S catalyst are as follows: Figure 2 As shown, increasing the sintering temperature leads to an increase in the original carbon-supported manganese-doped Cu. 1.96 Manganese-doped Cu in S catalyst 1.96 The S crystal phase transforms into the Cu9S5 crystal phase, while manganese is still doped into copper sulfides in the form of MnS.
[0106] (2) Scanning electron microscope
[0107] Carbon-supported manganese-doped Cu prepared in Example 1 1.96 The scanning electron microscopy (SEM) results of the S catalyst are as follows: Figure 3 As shown, the prepared carbon-supported manganese-doped Cu 1.96 The S catalyst basically retains the original Cu / Mn-BTC metal-organic framework octahedral morphology. After in-situ carbonization and sulfidation, the surface is rough and porous, which is beneficial to the mass transfer efficiency between the aqueous phase and the catalyst.
[0108] (3) Inductively Coupled Plasma Spectroscopy
[0109] Carbon-supported manganese-doped Cu prepared in Example 1 1.96 The inductively coupled plasma atomic emission spectrometry (ICP-MS) results of the S catalyst are shown in Table 1, indicating that the carbon-supported Mn-Cu 1.96 The manganese-copper ratio in the S catalyst is consistent with that used in the preparation of the original metal-organic framework. The in-situ sulfidation process did not result in metal loss, further demonstrating that manganese is doped into Cu via metal sulfides. 1.96 S in.
[0110] Table 1
[0111] <![CDATA[Mn-Cu 1.96 S / C]]> 17 9 23
[0112] Example 5
[0113] This embodiment provides carbon-supported manganese-doped Cu prepared in Example 1. 1.96 The application of S catalyst in the degradation of water pollutants by periodate. This example evaluates the active oxidizing substances generated after the catalyst activates periodate through a quenching experiment using simulated wastewater.
[0114] The simulated wastewater contained cycloheximine pollutants at a concentration of 300 mg / L. The active oxidants produced by the catalyst after catalyzing periodate were evaluated by adding tert-butanol (TBA), ethanol (Ethanol), carbon tetrachloride (CCl4), and dimethyl sulfoxide (DMSO).
[0115] Carbon-loaded manganese-doped Cu 1.96 The dosage of catalyst S was 100 mg / L, the dosage of periodate was 3 mmol / L, the dosage of TBA, Ethanol and CCl4 was 500 mmol / L, the dosage of DMSO was 2 mmol / L, and the total treatment time of the oxidation system was 15 min.
[0116] Results analysis:
[0117] The results of the quenching experiment of simulated wastewater are as follows Figure 4 As shown.
[0118] from Figure 4As can be seen from this, after adding excessive amounts of TBA, Ethanol, and CCl4, carbon-supported manganese-doped Cu... 1.96 The rate of cycloheximine degradation by S catalyst activation of periodate remained almost unchanged, indicating that hydroxyl radicals, iodate radicals, and superoxide anions are not the main active substances in this oxidation system; however, the degradation rate of cycloheximine decreased from 100% to 28% after the addition of DMSO, indicating that high-valence metals are the oxidants that degrade cycloheximine.
[0119] Furthermore, methyl phenyl sulfoxide (PMSO) was used as a probe substance to further verify whether the high-valence metal was an active substance. Figure 4 As can be seen from b, PMSO is rapidly converted to methylphenyl sulfone (PMSO2) within 1 min, with a conversion rate of 100%. This indicates that carbon-supported manganese-doped Cu 1.96 The S catalyst produces high-valence metals in the initial stage of the activation of periodate, which degrades pollutants, consistent with the quenching result.
[0120] Example 6
[0121] This embodiment provides carbon-supported manganese-doped Cu prepared in Example 1. 1.96 Application of S catalyst in the degradation of water pollutants by periodate. This example evaluates the efficiency of catalyst activation in the degradation of water pollutants by periodate using saline simulated wastewater.
[0122] The simulated wastewater contained cycloheximine pollutant at a concentration of 300 mg / L, as well as inorganic salts (NaCl, Na2SO4, NaNO3, Na2CO3, and NaH2PO4) at a concentration of 30 g / L.
[0123] Carbon-loaded manganese-doped Cu 1.96 The S catalyst dosage is 100 mg / L, with Cu 1.96 S and MnS served as controls. The periodate dosage was 3 mmol / L, and the total treatment time for the oxidation system was 15 min.
[0124] Results analysis:
[0125] Results of saline simulated wastewater experiments are as follows Figure 5 As shown.
[0126] from Figure 5 It can be observed that 30 g / L of five inorganic salts were added to carbon-supported manganese-doped Cu. 1.96 After S catalyzed the periodate system, the degradation rate of cycloheximine did not decrease significantly. The rate decreased slightly after the addition of Na₂CO₃, possibly because the combination of carbonate ions with hydrogen ions in the system increased the pH, thus slowing the rate. In contrast, Cu… 1.96The removal rates of cycloheximine by S and MnS decreased from 55% and 36% respectively without the addition of inorganic salts to below 15% after the addition of inorganic salts. This was achieved by using Cu alone. 1.96 S and MnS exhibit poor resistance to interference from inorganic ions. Overall, high concentrations of common inorganic anions did not affect the degradation of cyclohexylimine, thanks to carbon-supported manganese-doped Cu. 1.96 The high-valence metal active substances generated by S-activated periodate can react directly with pollutants without going through the free radical step, thus avoiding the quenching process of free radicals by anions.
[0127] Example 7
[0128] This embodiment provides carbon-supported manganese-doped Cu prepared in Example 1. 1.96 Application of S catalyst in the degradation of water pollutants by periodate.
[0129] In this embodiment, the water is wastewater from the production of a pharmaceutical intermediate. The nitrogen-containing heterocyclic pollutant is cyclohexylimine, with a concentration of 200–500 mg / L. The wastewater salinity is 2% (total dissolved solids concentration 20 g / L), and the pH is 8–9.
[0130] Manganese-doped Cu 1.96 The total dosage of catalyst S is 500 mg / L. Periodate is added in 30 separate doses of 5 mmol / L each time. The wastewater treatment is a continuous flow process that runs continuously for 30 days.
[0131] Results analysis:
[0132] Results of wastewater treatment in pharmaceutical intermediate production Figure 6 As shown.
[0133] from Figure 6 It can be observed that carbon-supported manganese-doped Cu 1.96 The S catalyst maintained a cyclohexylimine removal rate of over 90% for 30 consecutive days of operation, while commercially available Cu catalysts... 1.96 The initial removal rates of cyclohexylimine by S and MnS catalysts were only 51% and 15%, respectively, and their catalytic efficiency decreased significantly with continuous operation. This indicates that manganese doping and in-situ carbon composites not only improved the removal efficiency of Cu... 1.96 The catalytic activity of S is enhanced while ensuring the stability of the catalyst during long-term operation, which is beneficial for the application of the catalyst in practical engineering.
[0134] In addition, compared with similar Fenton techniques, carbon-loaded manganese-doped Cu 1.96 S-catalyst activation of periodate treatment for saline chemical wastewater also has significant advantages, because the non-radical pathways generated in this process are not affected by salt content.
Claims
1. A carbon-supported manganese-doped Cu 1.96 Application of S catalyst in the degradation of water pollutants by periodate, the catalyst comprising: Porous carbon layer; The active component Cu distributed on the porous carbon layer 1.96 S; Doped with the active ingredient Cu 1.96 The active ingredient MnS in S; The carbon-supported manganese-doped Cu 1.96 The preparation method of the S catalyst includes: using Cu / Mn co-grown Cu / Mn-BTC metal-organic framework as a precursor, the precursor and organic sulfur source are adsorbed and mixed under oxygen-free conditions and then sintered under oxygen-free conditions.
2. The application according to claim 1, characterized in that, The water body includes saline water bodies.
3. The application according to claim 2, characterized in that, The concentration of the salt is 5~35 g / L.
4. The application according to any one of claims 1-3, characterized in that, The preparation method includes the following steps: S1, copper and manganese salts are added to an ethanol solution; after dissolution, pyromellitic acid and N,N-dimethylformamide are added; when the solution becomes turbid, pure water is added and stirred; the mixed solution after stirring is hydrothermally heated, washed and dried to obtain the metal-organic framework precursor Cu / Mn-BTC. S2, the metal-organic framework precursor Cu / Mn-BTC and 2,5-diaminobenzenesulfonic acid obtained in S1 are added to a mixed solution of ethanol and methanol, adsorbed in a hydrogen-argon mixed gas, and the ethanol and methanol in the adsorbed mixed liquid are removed to obtain a precursor mixed powder. S3. The precursor mixture powder obtained in S2 is transferred to a tube furnace and sintered in an oxygen-free environment under argon protection at a temperature of 500–700 °C for 3–6 hours at a heating rate of 2–4 °C / min to obtain carbon-supported manganese-doped Cu. 1.96 S catalyst.
5. The application according to claim 4, characterized in that, In S1, The molar ratio of Cu:Mn:BTC is 2:1:4; And / or the amount used is 2 to 3 ml relative to 0.001 mol of Mn,N,N-dimethylformamide; The volume ratio of DMF, ethanol and pure aqueous solution is 1:(1.5~2):(1.2~1.5); And / or in S2, The mass ratio of the metal-organic framework precursor Cu / Mn-BTC to 2,5-diaminobenzenesulfonic acid is 1:(2.5~3.5); The volume ratio of ethanol to methanol in a mixed solution of ethanol and / or ethanol and methanol is 1:(1.5~3); In the hydrogen-argon mixture and / or the mass fraction of hydrogen is 2% to 10%.
6. The application according to claim 5, characterized in that, In S1, The copper salt includes any one or more of copper chloride, copper sulfate, and copper nitrate. And / or the manganese salt includes any one or more of manganese chloride, manganese sulfate, and manganese nitrate.
7. The application according to claim 5 or 6, characterized in that, In S1, The stirring includes stirring at 25~40℃ for 6~10 hours; And / or the hydrothermal treatment includes hydrothermal treatment at 100~130℃ for 16~32 hours; And / or in S2, The adsorption time includes 6 to 12 hours; And / or in S3, The sintering temperature is 550℃~700℃; And / or the sintering time is 3.5 to 6 hours; And / or the heating rate is 2, 3 or 4 °C / min.
8. The application according to claim 7, characterized in that, In S1, The copper salt includes copper chloride; the manganese salt includes manganese chloride; The amount of N,N-dimethylformamide used relative to 0.001 mol of Mn is 2.5 ml; the volume ratio of DMF, ethanol and pure aqueous solution is 1:1.6:1.3; The stirring includes stirring at 30°C for 8 hours; the hydrothermal treatment includes hydrothermal treatment at 120°C for 24 hours. In S2, The mass ratio of the metal-organic framework precursor Cu / Mn-BTC to 2,5-diaminobenzenesulfonic acid is 1:3; the volume ratio of ethanol to methanol in the ethanol-methanol mixed solution is 1:2; and the hydrogen-argon mixed gas contains 5% hydrogen by mass. The adsorption time includes 10 hours; In S3, The sintering temperature was 550℃, the sintering time was 3.5 hours, and the heating rate was 3℃ / min.
Citation Information
Patent Citations
Method for quickly removing refractory organic matter in wastewater through activation of persulfate by hollow cobalt-rich bimetallic sulfide
CN109092329A
Hollow flower-ball-shaped composite material of manganese-doped transition metal sulfide and preparation method
CN117476891A